Practitioner Review: The effects of atypical antipsychotics and mood stabilisers in the treatment of depressive symptoms in paediatric bipolar disorder. (5th May 2017) - Atkin, Tobias; Nuñez, Nicolas; Gobbi, Gabriella
Abstract : Background: The management of depressive and mixed symptoms in children and adolescents with bipolar disorder (BD) remains a matter of debate. The goal of this review is, thus, to systematically examine the impact of atypical antipsychotics (AAPs) and mood stabilisers in the treatment of bipolar depression and/or mixed states. Methods: A literature search was conducted for studies assessing the efficacy of pharmacological treatments for bipolar disorder type I, type II and not otherwise specified with a recent depressive, mixed or manic episode (with depressive symptoms) following DSM‐IV criteria in children and adolescents as either acute or maintenance treatment. The databases searched were PubMed/Medline, Google Scholar and Tripdatabase, as well as ClinicalTrials.gov. The search was limited to clinical trials, systematic reviews, meta‐analyses and open‐label trials published in the English language between the years 2000 and 2015. Sixty clinical studies were found assessing the efficacy of mood stabilisers and AAPs in paediatric BD. Fifteen studies were not included in the primary analysis because they did not assess depressive symptomology/include scores on rating scales of depressive symptoms (Online Supplementary Material). Results: There is sufficient evidence for a Grade A recommendation of the use of olanzapine plus fluoxetine at reducing depressive symptoms in bipolar depression and of quetiapine at high doses for depressive symptoms occurring during mixed episodes. Importantly, even though monotherapy with aripiprazole, risperidone, valproate and lithium was effective at controlling mania, these drugs were not effective at reducing depressive symptoms (level A evidence for nonrecommendation). Conclusions: These results mostly overlap with the approved treatments for bipolar depression in adults.